PROSES INTERNALISASI NILAI SELF-ESTEEM DALAM PENGUATAN PENDIDIKAN KARAKTER SISWA KELAS IV DI SDN 2 MENTENG - Labibah, Sabilah; Maulin Maulin; Tri Cahyaning Utami; Surawan Surawan (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study was motivated by the importance of strengthening character education among elementary school students through the development of self-esteem, given the role of self-confidence, a sense of self-worth, and responsibility in shaping positive behavior and constructive social interactions. This study aims to analyze the process of internalizing self-esteem values in strengthening character education among fourth-grade students at SDN 2 Menteng. The study employs a quantitative approach with a survey design to obtain an overview of self-esteem internalization, using numerical data collected via a structured questionnaire containing 15 statements based on indicators of self-confidence, self-worth, responsibility, and positive behavior, supplemented by interview data. The research subjects were all fourth-grade students selected using a saturation sampling technique. The instrument’s validity and reliability were tested prior to use, while the data were analyzed using descriptive statistical analysis techniques to describe trends in student responses. The research findings indicate that students have internalized the value of self-esteem quite well, as evidenced by their self-confidence, self-respect, sense of responsibility, social awareness, and ability to accept feedback and improve themselves; however, further reinforcement is needed regarding their courage to express opinions and their belief in their own potential. The implications of this study confirm that strengthening self-esteem through the cultivation of positive behaviors and teacher guidance can serve as an effective strategy in character education grounded in moral values and Islamic religious education in elementary schools.